In Vitro Activity of Ceftazidime-Avibactam against Clinical Isolates of Enterobacteriaceae and Pseudomonas aeruginosa Collected in Latin American Countries: Results from the INFORM Global Surveillance Program, 2012 to 2015 - Karlowsky, James A. (Antimicrob Agents Chemother, 2019)
The International Network for Optimal Resistance Monitoring (INFORM) global surveillance program collected clinical isolates of Enterobacteriaceae (n = 7,665) and Pseudomonas aeruginosa (n = 1,794) from 26 medical centers in six Latin American countries from 2012 to 2015. The in vitro activity of ceftazidime-avibactam and comparators was determined for the isolates using the Clinical and Laboratory Standards Institute (CLSI) reference broth microdilution method. Enterobacteriaceae were highly susceptible (99.7%) to ceftazidime-avibactam, including 99.9% of metallo-β-lactamase (MBL)-negative isolates; 87.4% of all P. aeruginosa isolates and 92.8% of MBL-negative isolates were susceptible to ceftazidime-avibactam. Susceptibility to ceftazidime-avibactam ranged from 99.4% to 100% for Enterobacteriaceae and from 79.1% to 94.7% for P. aeruginosa when isolates were analyzed by country of origin. Ceftazidime-avibactam inhibited 99.6% to 100% of Enterobacteriaceae isolates that carried serine β-lactamases, including extended-spectrum β-lactamases (ESBLs), AmpC cephalosporinases, and carbapenemases (KPC and OXA-48-like) as well as 99.7%, 99.6%, 99.5%, and 99.2% of MBL-negative isolates demonstrating ceftazidime-nonsusceptible, multidrug-resistant (MDR), meropenem-nonsusceptible, and colistin-resistant phenotypes, respectively. Among carbapenem-nonsusceptible isolates of P. aeruginosa (n = 750), 14.7% carried MBLs with or without additional acquired serine β-lactamases, while in the majority of isolates (70.0%), no acquired β-lactamase was identified. Ceftazidime-avibactam inhibited 89.5% of carbapenem-nonsusceptible P. aeruginosa isolates in which no acquired β-lactamase was detected. Overall, clinical isolates of Enterobacteriaceae collected in Latin America from 2012 to 2015 were highly susceptible to ceftazidime-avibactam, including isolates that exhibited resistance to ceftazidime, meropenem, colistin, or an MDR phenotype. Country-specific variations were noted in the susceptibility of P. aeruginosa isolates to ceftazidime-avibactam.